Nickel-Catalyzed Asymmetric Borylative Coupling of 1,3-Dienes with Aldehydes - Ma, Jin-Tao; Xiao, Li-Jun (Synlett, 2024)
The nickel-catalyzed borylative coupling of aldehydes and 1,3-dienes with diboron reagents offers an efficient method for synthesizing valuable homoallylic alcohols from easily accessible starting materials. However, achieving enantioselectivity in this reaction has been a significant challenge. We discuss our recent report on the first example of a nickel-catalyzed enantioselective borylative coupling of aldehydes with 1,3-dienes, employing a chiral spiro-phosphine–oxazoline ligand. Notably, by utilizing (E)-1,3-dienes or (Z)-1,3-dienes, we can reverse the diastereoselectivity, yielding either anti- or syn-products, respectively.
Keywords: borylative coupling; homoallylic alcohols; nickel catalysis; spiro compound; enantioselectivity; diastereoselectivity